Effect of model simplification through manual reduction in number of surfaces on room acoustics simulation - Abd Jalil, Nurul Amira; Che Din, Nazli; Keumala, Nila; Abdul-Razak, Asrul Sani (Faculty of Built Environment, University of Malaya, 2019)
Model simplification is an important step in room modelling for acoustics simulation. Various simplification algorithms were previously suggested. However, they are highly demanding methods, which are more suitable for large complicated spaces. As this paper focused on small size open-plan office (OPO) spaces, basic modelling and manual simplification processes were used. The aim is to find the optimum level of model simplification through a manual reduction in number of surfaces. Parallel to this aim, the objective is to examine the effects of the change in model detail level on selected acoustical parameters in six OPOs. Construction of models started with the most detailed model. Simplified models were developed by gradually reducing the number of surfaces. Simulation on RT, STI and decay in SPL were done and compared to the measured data. The study found that models with up to 80% reduction in number of surfaces can still produce plausible simulation results. © 2019, University of Malaya. All rights reserved.